Combined effects of glycerol monostearate and surface-applied lipids on noodle quality - Zehua Zhang; Yiyuan Zou; Zhiling Tang; Haoran Luo; Yun Zhou; Jia Chen; Guohua Zhao (Food Chemistry, 2026)

The mechanism underlying the quality deterioration effects of buckwheat flour on normal noodles: insights from its component perspectives - Zhiling Tang; Yiyuan Zou; Zehua Zhang; Haoran Luo; Fayin Ye; Guohua Zhao (Food Research International, 2026)

Protein transition induced by heat-moisture treatment modulated dough properties: Insights from multiscale structure and quantitative proteomics - Yiyuan Zou; Zehua Zhang; Zhiling Tang; Haoran Luo; Fayin Ye; Guohua Zhao (Food Hydrocolloids, 2026)

Luteolin and glycitein from Codonopsis pilosula ameliorate age-related locomotor decline in C. elegans via DAF-16-dependent but autophagy-divergent pathways - Yan Zhuang; Lulu Yi; Can Zhang; Lu Chen; Ajia Chen; Gong Tang; Zhiling Li; Zhongliang Hu (Biogerontology, 2026)

Interaction of glyceryl monostearate with gluten: Adsorption behavior, structural changes, and functional implications on dough properties - Zehua Zhang; Yiyuan Zou; Zhiling Tang; Haoran Luo; Yun Zhou; Jia Chen; Guohua Zhao (Food Chemistry, 2026)

Enhanced impact of future temperature on Northern Hemisphere snowfall - Lina Liu; Liping Zhang; Qin Zhang; Gangsheng Wang; Zhiling Zhou; Xiao Li; Zhenyu Tang; Jun Xia (Journal of Hydrology, 2025)

Quality improvements of buckwheat noodles by Artemisia sphaerocephala Krasch gum: Effects of pre-hydration and addition mode - Zhiling Tang; Yiyuan Zou; Haoran Luo; Zehua Zhang; Fayin Ye; Guohua Zhao (Food Chemistry, 2025)

Daily runoff simulation in humid regions using the entropy-weighted ensemble learning models - Zhenyu Tang; Liping Zhang; Chen Hu; Yaze Li; Gangsheng Wang; Zhiling Zhou; Xiao Li; Zhengfeng Bao; Hui Cao; Benjun Jia (Environmental Modelling & Software, 2025)

Quality improvements of reconstituted noodles by pre-hydrating gluten: Insights at different levels - Haoran Luo; Zehua Zhang; Yiyuan Zou; Zhiling Tang; Miaomiao Gu; Yun Zhou; Guohua Zhao (Food Chemistry, 2025)

The application of monoglycerides to improve the quality of fresh noodles: Discerning the roles of acyl chain length and dispersity - Zehua Zhang; Yiyuan Zou; Zhiling Tang; Haoran Luo; Yun Zhou; Jia Chen; Guohua Zhao (Food Chemistry, 2025)

Altered Intrinsic Brain Activity in Ischemic Stroke Patients Assessed Using the Percent Amplitude of a Fluctuation Method - Jurong Ding; Zhiling Tang; Yihong Liu; Qiang Chen; Ke Tong; Mei Yang; Xin Ding (Brain Topography, 2024)

The underappreciated role of fugitive VOCs in ozone formation and health risk assessment emitted from seven typical industries in China - Zhiling Liang; Yunjiang Yu; Bingbing Sun; Qian Yao; Xihua Lin; Yongsheng Wang; Jianping Zhang; Yingzi Li; Xuefeng Wang; Zhengzheng Tang; Shexia Ma (Journal of Environmental Sciences, 2024)

Construction of zinc-oxygen double vacancies BiOCl/ZnS Z-scheme heterojunction and photocatalytic degradation of norfloxacin - Wujian Zhang; Zhiling Huang; Lianyang Zhang; Yue Meng; Zheming Ni; Haodong Tang; Shengjie Xia (Journal of Environmental Chemical Engineering, 2023)

MIL-68 (In)-derived In2O3@TiO2 S-scheme heterojunction with hierarchical hollow structure for selective photoconversion of CO2 to hydrocarbon fuels - Yingli Wang; Wenjie He; Jing Xiong; Zhiling Tang; Yuechang Wei; Xiong Wang; Hui Xu; Xiao Zhang; Zhen Zhao; Jian Liu (Fuel, 2023)

LncRNA MAFG-AS1 regulates miR-125b-5p/SphK1 axis to promote the proliferation, migration, and invasion of bladder cancer cells - Chenye Tang; Yuntao Wu; Xiao Wang; Kean Chen; Zhiling Tang; Xiao Guo (Human Cell, 2021)
MAFG-AS1 is an oncogenic lncRNA in multiple types of cancer. However, its role in bladder cancer (BC) remains unclear. The present study aimed to investigate the function of MAFG-AS1 in BC. BC and paired non-tumor tissues were collected. Two BC cell lines HT01197 and HT-1376 were used. Dual luciferase activity assay, RT-qPCR, western blot, CCK-8, transwell invasion assay, and wound healing assay were performed. We found that MAFG-AS1 was significantly up-regulated in BC tissues and predicted a poor survival rate. MAFG-AS1 interacted with miR-125b-5p. However, the expression levels of MAFG‑AS1 and miR-125b-5p were not obviously correlated in BC tissues, and MAFG‑AS1 and miR-125b-5p did not regulate the expression of each other. Interestingly, we found that SphK1, a downstream target of miR-125b-5p, was negatively correlated with miR-125b-5p, while it was positively correlated with MAFG-AS1 across BC tissues. In addition, overexpression of MAFG‑AS1 upregulated the expression of SphK1 in BC cells, and attenuated the inhibitory effects of miR-125b-5p on the expression of SphK1. Functional assays showed that overexpression of MAFG‑AS1 promoted BC cell proliferation, migration, and invasion, while its effects were attenuated by overexpression of miR-125b-5p. Moreover, overexpression of miR-125b-5p inhibited BC cell proliferation, migration, and invasion, while its effects were alleviated by overexpression of SphK1. Taken together, our findings demonstrated that MAFG-AS1 has an oncogenic role in BC by regulating the miR-125b-5p/SphK1 axis. MAFG-AS1 might serve as a good diagnostic marker and a potential therapeutic target of BC.